Jacques Backyard - Ferreira, A.; Raposo, I.; Fernandes, L. (Open Schools Journal for Open Science, 2020)
From a letter to the School's director “What I think about my school”, students identified problems and designed a project in order to have direct intervention in the solution. Under the theme "Biodiversity", the project aimed to create an "edible garden" at school and involved different activities: planting trees, identifying the existing ones, growing vegetables, composting and collecting rainwater for irrigation, where some of them. The construction of the gardens respected the underground life and the planting was done taking into account the intercropping of plants. Whenever possible, the project was linked to the students' curriculum. The project also had an artistic aspect: students and elderly people graffitied one of the walls next to the vegetable gardens, taking advantage of an autarchy project entitled “Active aging”.